Weighted Word Affinity Graph for Betterment of Spatial Information Descriptors - Yadav, Poonam (International Journal of Computer Sciences and Engineering, 2014)
Document analysis/ retrieval system plays crucial role to strengthen any information retrieval system. There are various processing stages associated with a document analysis system, such as feature extraction stage, semantic representation stage, dimensionality reduction stage and similarity measure stage. Researchers are contributing well in every stage to improve the performance of the document analysis system. This short paper considers word affinity graph/ matrix for further improvement so that semantic representation can be given more precisely. This is accomplished by incorporating weight component in the word affinity matrix to provide significance for degree of distribution. Theoretical study on both word affinity matrix and weighted word affinity matrix shows the significance offering by them on widely distributed document terms.